1992
DOI: 10.1128/iai.60.9.3824-3829.1992
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to outer membrane antigens of Moraxella catarrhalis in children with otitis media

Abstract: The systemic and local antibody responses to homologous strains of MoraxeUla catarrhalis were investigated in 14 children with otitis media. A total of 8 children (57%) demonstrated a rise in serum antibody of the immunoglobulin G (IgG) (5 of 14), IgM (5 of 14), or IgA (6 of 14) classes of immunoglobulin to outer membrane antigens. Local antibody consisted of IgG (100%), IgM (29%v), and IgA (71%). The IgG and IgA specific antibody present in middle-ear effusions appeared to represent local production rather th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 40 publications
(42 reference statements)
1
30
0
Order By: Relevance
“…All animals were challenged 5 weeks after the initial immunization with either the homologous or a heterologous strain. To each challenge group, untreated control animals were added (n=5, 5,6,6). Otomicroscopy was performed prior to immunization (day 0).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…All animals were challenged 5 weeks after the initial immunization with either the homologous or a heterologous strain. To each challenge group, untreated control animals were added (n=5, 5,6,6). Otomicroscopy was performed prior to immunization (day 0).…”
Section: Experimental Designmentioning
confidence: 99%
“…The targets for a protective immune response have not been identified, but the homogeneous composition of the outer membrane proteins and the lipopolysaccharide of M. cutarrhalis suggest that an antibody response to one strain may protect against others (1,24). However, the immune response to the organism seems to be poor, and young children fail to develop a systemic antibody response in a uniform manner after a middle ear infection (5,15).…”
mentioning
confidence: 99%
“…cutarrhalis during infection have shown that approximately half the patients exhibit a response to antigens of this organism (2, 3, 4, 7,17). Young children with otitis media also failed to respond immunologically to M. catarrhalis in a uniform manner (8). Antibodies against M .…”
Section: Discussionmentioning
confidence: 99%
“…This finding may indicate that IgG3 is not protective in these patients who may then suffer repeated infections caused by M. catarrhalis. IgA and IgM responses were limited to a few patients in the present study. Previous studies have pointed to the lack of a regular response of these antibody classes (8,9). For the serological diagnosis of infections with M. catarrhalis the demonstration of the IgG3 response to outer membrane proteins appears to offer improved sensitivity as compared to the whole-cell ELI-SA.…”
Section: Discussionmentioning
confidence: 99%
“…It is also associated with respiratory infection in older adults, especially exacerbations of chronic obstructive pulmonary disease (Black & Wilson, 1988;Sethi & Murphy, 2001). A rise in serum antibody against M. catarrhalis has been reported in these patients (Chapman et al, 1985;Black & Wilson, 1988;Faden et al, 1992;Christensen, 1999;Bakri et al, 2002). Thus, a vaccine that can reduce or prevent M. catarrhalis infection will benefit both young and old.…”
Section: Introductionmentioning
confidence: 99%